Rethinking English Teaching in the AI Era: English Educators' AI Literacy and Practice - Bontisesari Bontisesari; Renta Renta; Irma Rasita Gloria Barus (Universitas Nurul Jadid, 2026)
This study examines English educators’ AI literacy and teaching practices in the AI era, focusing on how English teachers and English lecturers understand, use, and ethically manage AI in English language teaching. Adopting a qualitative case study design, the study involved questionnaire data from 27 English educators and semi-structured interviews with five participants from diverse educational contexts. The questionnaire explored educators’ AI awareness, pedagogical use of AI, and ethical practices, while interviews provided in-depth insights into educators’ experiences and professional decision-making. Questionnaire data were analyzed descriptively, and interview data were analyzed thematically. The findings indicate that English educators demonstrate moderate AI awareness and strong ethical sensitivity; however, their pedagogical use of AI remains cautious, selective, and largely teacher-mediated. AI tools were primarily used for instructional preparation and text-based language support, particularly in writing and reading. Student-facing AI use and assessment-related integration were limited due to concerns about academic integrity, overreliance, and learning quality. Despite high ethical awareness, many educators reported uncertainty in evaluating AI-assisted student work and establishing clear boundaries for acceptable AI use. The study concludes that English educators’ AI literacy is pedagogical and contextual rather than primarily technical. Meaningful AI integration in ELT requires professional development and institutional support that prioritize pedagogical judgment and ethical guidance over technical training alone.